Indian Economy: Current Trends & Future - SHARMA, NIKET (The journal of contemporary issues in business and government, 2021)
India has increasingly been regarded as an engine that will power future global development. This is good reason to look at the economic prospects of India over the current decade. The Indian economy is the fastest growing major economy and in the coming years it is expected to grow faster. During 2018-19, however, the economy of India appears to have slowed significantly. The proximate factors responsible for this slowdown include rising private consumption growth, a modest increase in fixed investment, and exports that are quite. On the supply side, the challenge is to reverse the agricultural sector’s decline in growth and maintain industry growth. On the external front, the current account deficit as a ratio to GDP is likely to decline in 2018-19, thus reducing the economy’s leakage of growth momentum. Monetary policy has sought to provide growth momentum with a fillip through repo rate cuts and bank liquidity easing. Low inflation has provided the room for this monetary easing in 2018-19, although it has started to rise in the last few months of the year. Growth has tied up, deflation has decreased, budget and trade deficits have shrunk. The Government of India has also adopted policies and reforms to promote investment, increase efficiency and ensure monetary stability. The strong long-term growth potential of India, driven by demographics, urbanisation, and productivity- enhancing reforms, nevertheless indicates that trade expansion between china and india will continue in the upcoming months.